Faktor determinan pada financial well being pekerja dewasa di Jakarta - Julius Pratama; Sawidji Widoatmodjo (Universitas Tarumanagara, 2023)
This research aims to determine whether the financial well-being of adult workers in Jakarta is influenced by financial literacy, financial behaviour, financial stress, and internal locus of control (LOC). This study utilizes primary data with the target population being adult workers residing in Jakarta. The data collection process was conducted by distributing an online questionnaire through Google Forms. The sampling method used is non-probability sampling with convenience sampling type, with a total of 241 respondents collected. The data analysis technique employed is Structural Equation Modeling (SEM) using SmartPLS software version 3.2.9. The results of this research indicate that financial literacy has a positive but not significant influence, financial behaviour and internal locus of control have a significant positive influence, while financial stress has a significant negative influence on the financial well-being of adult workers in Jakarta. Tujuan dari penelitian ini adalah untuk mengetahui apakah financial well-being pekerja dewasa di Jakarta dipengaruhi oleh financial literacy, financial behaviour, financial stress, dan internal locus of control (LOC). Penelitian ini menggunakan data primer dengan target populasi adalah pekerja dewasa yang berdomisili di Jakarta. Proses pengumpulan data dilakukan dengan menyebarkan kuesioner secara online melalui media Google Form. Metode pengumpulan sampel menggunakan non-probability sampling jenis convenience sampling dengan responden yang terkumpul berjumlah 241 responden. Teknik analisis data yang digunakan adalah Structural Equation Modeling (SEM) dengan software SmartPLS versi 3.2.9. Hasil penelitian ini mendapatkan bahwa financial literacy berpengaruh positif tetapi tidak signifikan, financial behaviour dan internal locus of control berpengaruh positif signifikan sedangkan financial stress berpengaruh negatif signifikan terhadap financial well-being pekerja dewasa di Jakarta.